Multiple cerebral infarctions in ROS1‐rearranged lung adenocarcinoma. Issue 9 (26th August 2021) - Ikushima, Hiroaki; Hiraishi, Yoshihisa; Toriumi, Kanto; Ando, Takahiro; Tamiya, Hiroyuki; Ishida, Junichi; Amano, Yosuke; Kage, Hidenori; Tanaka, Goh; Nagase, Takahide
Abstract: Rearrangements of specific tyrosine kinases are associated with an elevated risk of venous thrombosis in lung adenocarcinoma, although their effects on arterial thrombosis have not been fully elucidated. Here, we report two cases of ROS proto‐oncogene 1 ( ROS1 )‐rearranged lung adenocarcinoma with cerebral infarction during the peri‐diagnostic period. Two cases took contrasting clinical courses: one patient could not receive targeted therapy because of a significant decline in performance status, whereas in the other patient, the performance status was maintained and targeted therapy drastically reduced the tumour size. Our cases suggest close monitoring could be considered in the selected cohort. Abstract : In Case 1, after 1 day of bronchoscopy, the patient developed neurological symptoms and brain magnetic resonance imaging showed multiple acute cerebral infarction.